Not Quite Shipshape: How Better Reputations Can Lead to Worse Performance - Desai, Vinit M. (Journal of Management Studies, 2025)
AbstractResearch suggests that firms with good reputations will work to protect them, as good reputations are assets that attract resources and facilitate market exchanges. But good reputations do not just attract resources and facilitate exchanges; they can also buffer firms from scrutiny. Therefore, this study asks whether organizations with good reputations will still perform well, even if they are less likely to be watched or held accountable for doing poorly. The study bounds its focus to a form of performance that depends on external oversight, in this case through the regulatory governance process. The theory suggests that higher regulatory reputations, as measured through increases in ratings, will lead to weaker monitoring – which, in turn, allows performance to decline in the regulated domain. An analysis of public health outcomes in the cruise travel industry provides support for these predictions. Tests of moderating hypotheses suggest that the direct effect of ratings on performance is stronger when regulators have more power over the organization, and when the organization is not already under scrutiny for poor performance on other ancillary dimensions.